The Circadian Oscillator of the Cerebellum: Triiodothyronine Regulates Clock Gene Expression in Granule Cells in vitro and in the Cerebellum of Neonatal Rats in vivo - Bering, Tenna; Hertz, Henrik; Rath, Martin Fredensborg (Frontiers in Physiology, 2021)
The central circadian clock resides in the suprachiasmatic nucleus (SCN) of the hypothalamus, but an SCN-dependent molecular circadian oscillator is present in the cerebellar cortex. Recent findings suggest that circadian release of corticosterone is capable of driving the circadian oscillator of the rat cerebellum. To determine if additional neuroendocrine signals act to shape cerebellar clock gene expression, we here tested the role of the thyroid hormone triiodothyronine (T3) in regulation of the cerebellar circadian oscillator. In cultured cerebellar granule cells from mixed-gender neonatal rats, T3 treatment affected transcript levels of the clock genes Per2, Arntl, Nr1d1and Dbp, suggesting that T3 acts directly on granule cells to control the circadian oscillator. We then used two different in vivo protocols to test the role of T3 in adult female rats: Firstly, a single injection of T3 did not influence clock gene expression in the cerebellum. Secondly, we established a surgical rat model combining SCN lesion with a programmable micropump infusing circadian physiological levels of T3; however, rhythmic infusion of T3 did not reestablish differential clock gene expression between day and night in SCN lesioned rats. To test if the effects of T3 observed in vitro were related to the developmental stage, acute injections of T3 were performed in mixed-gender neonatal rats in vivo; this procedure significantly affected cerebellar expression of the clock genes Per1, Per2, Nr1d1and Dbp. Developmental comparisons showed rhythmic expression of all clock genes analyzed in the cerebellum of adult rats only, whereas T3 responsiveness was limited to neonatal animals. Thus, T3 shapes cerebellar clock gene profiles in early postnatal stages, but it does not represent a systemic circadian regulatory mechanism linking the SCN to the cerebellum throughout life.